Low switching stress DC-DC converter with capability of high voltage gain for low voltage energy sources. Issue 2 (3rd April 2017) - Sathyan, Shelas; Suryawanshi, H. M.; Ballal, M. S.; Shitole, A. B.
Abstract: A soft-switched integrated boost-forward converter with switched capacitor voltage extension cell for low voltage energy sources is proposed. Extended switched capacitor voltage multiplier circuit is incorporated at the secondary side of the forward type coupled inductor. Switched capacitors of the voltage extension cell, charge in parallel through the coupled inductor when the main switch is OFF and discharge to the output in series when the main switch is ON. Thus high voltage step-up is achieved and the voltage stress on the MOSFETs and diodes are reduced. Here, the auxiliary MOSFETs switch helps to realize zero voltage switching turn ON of the MOSFET switches and clamp the voltage across the switches. Modeling and steady state analysis of the converter is provided. A 400 W experimental prototype is build and tested in laboratory. Measured full load efficiency of the converter is 94.29% and highest efficiency is 96.03%.